Macroevolution of hoverflies (Diptera : Syrphidae): the effect of using higher-level taxa in studies of biodiversity, and correlates of species richness - Katzourakis, A; Purvis, A; Azmeh, S; Rotheray, G; Gilbert, F (2001)
We test a near-complete genus level phylogeny of hoverflies (Diptera: Syrphidae) for consistency with a null model of clade growth having uniform probabilities of speciation and extinction among contemporaneous species. The phylogeny is too unbalanced for this null model. Importantly, the degree of imbalance in the phylogeny depends on whether the phylogeny is analysed at the genus level or species level, suggesting that genera ought not to be used uncritically as surrogates for species in large-scale evolutionary analyses. Tests for a range of morphological, life-history and ecological correlates of diversity give equivocal results, but suggest that high species-richness may be associated with sexual selection and diet breadth. We find no correlation between species-richness and either body size or reproductive rate.